SOMATIC EMBRYOGENESIS AND PLANT REGENERATION FROM CALLUS AND SUSPENSION CULTURES OF IPHIONA MUCRONATA (FORSSK) - Al-Gendy, Amal A.; Bakr, Riham O.; El-gindi, Omayma D. (European Scientific Journal, ESJ, 2013)
A protocol was designed for plant regeneration of Iphiona mucronata from embryogenic callus via somatic embryogenesis to enable micro propagation of this endangered plant. The embryogenic callus was induced using seedling cultured for nine months on Murashig and Skoog medium (MS) supplemented with 0.1 mg l-1 naphthalene acetic acid (NAA), 0.1 mg l-1 kinetin (Kn) and 5 mg l-1 ascorbic acid and incubated in the dark followed by growing on hormone free medium. Transfer of developed embryos to MS medium supplemented with 0.5 mg l-1 kinetin induced shoot formation. Four treatments were further tried for plant development by using indole acetic acid (IAA) or indole butyric acid (IBA) alone or in combination with kinetin. The results showed that 2 mg l-1 IAA was the best for in vitro plantlet regeneration. Embryogenic suspension was induced by transfer of embryogenic callus to liquid medium having the same composition followed by hormone free medium where different stages of embryos were monitored. Shoots were developed upon transfer to liquid medium supplemented with 0.5 mg l-1 Kn. However, no further development appeared upon transfer to semi solid medium containing different phytohormones. Embryogenic callus showed the highest phenolic contents when compared with embryogenic suspension, regenerated plantlets and the parent plant while flavonoids were detected only in embryogenic callus.